Proyecto de inversión para la comercialización de frutas en máquinas expendedoras en la ciudad de Guayaquil. - Bautista Rodríguez, Andrea Soledad (2010)
The present work performs a feasibility analysis for the investment of creating a company dedicated to sell cut fruits packaged under modified atmosphere pressure and marketed through the use of vending machines within the city of Guayaquil. Assuming that there is a need for a healthy diet, fruits present themselves as the base product family that enjoys being in a daily diet, which is very common to find health problems due to the environment in which we travel and because of that there are diseases like diabetes, cholesterol or obesity caused by poor diet and lack of nutrients, many of them found mainly in fruits. The product consist in packaging a portion of different fruits to offer which are washed, peeled, cut and packaged in small plastic containers with an innovative modified atmosphere which maintains the freshness and quality of fruit for a longer time to be sold directly to consumers through vending machines located in universities and commercial centers of the main port of Ecuador. Thus appearing such as a snack that satisfies the requirements mentioned in a more rapid and accessible at an affordable price of USD1. Using tools such as market research, technical and financial analysis, it is clear that the investment project is viable in the market established thanks to the different strategies proposed, as well as the demand is estimated to have.